Learning and collaboration technologies : design, development and technological innovation : 5th International Conference, LCT 2018, held as part of HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I - (:unkn) unknown (My University, 2018)
This two-volume set LNCS 10924 and 10925 constitute the refereed proceedings of the 5th International Conference on Learning and Collaboration Technologies, LCT 2018, held as part of the 20th International Conference on Human-Computer Interaction, HCII 2018, in Las Vegas, NV, USA in July 2018. The 1171 papers presented at HCII 2018 conferences were carefully reviewed and selected from 4346 submissions. The papers cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of applications areas. The papers in this volume are organized in the following topical sections: designing and evaluating systems and applications, technological innovation in education, learning and collaboration, learners, engagement, motification, and skills, games and gamification of learning, technology-enhanced teaching and assessment, computing and engineering education.
Keywords: Education; E-learning; Human-Computer Interaction (HCI); Artificial intelligence; Computer aided instruction; Computer networks; Software engineering; User interfaces; Computer-Aided Design (CAD); Semantics; Data security; Information technology; Robotics; Learning experience; Learning environments; Education computing; Virtual reality; Augmented reality systems; Security and policies; Online environments